2008
DOI: 10.1038/clpt.2008.202
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Regulation of Hepatic Drug-Metabolizing Enzyme Activity During Adolescence

Abstract: Activities of drug metabolizing enzymes (DME) are known to change throughout the course of physical and sexual maturation with the greatest variability noted during infancy and adolescence. The mechanisms responsible for developmental regulation of DME are currently unknown. However, the hormonal changes of puberty/adolescence provide a theoretical framework for understanding biochemical regulation of DME activity during growth and maturation. Important information regarding potential influences of growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 72 publications
(73 reference statements)
1
47
0
3
Order By: Relevance
“…However, developmental profiles of DME expression and activity closely reflect that of major shifts in hormonal levels associated with growth and sexual maturation (Leeder and Kearns, 1997). Growth and/or sex hormones can potentially serve as biochemical regulators of DME expression through interaction with nuclear hormone receptors such as the pregnane X receptor and/or the constitutive androstane receptor (Kennedy, 2008). Hosokawa and Satoh (1988) reported that the expression of carboxylesterase isoenzymes RL1 and RH1 in the liver of hypophysectomized rats was significantly decreased after the treatment of HGH.…”
Section: Discussionmentioning
confidence: 99%
“…However, developmental profiles of DME expression and activity closely reflect that of major shifts in hormonal levels associated with growth and sexual maturation (Leeder and Kearns, 1997). Growth and/or sex hormones can potentially serve as biochemical regulators of DME expression through interaction with nuclear hormone receptors such as the pregnane X receptor and/or the constitutive androstane receptor (Kennedy, 2008). Hosokawa and Satoh (1988) reported that the expression of carboxylesterase isoenzymes RL1 and RH1 in the liver of hypophysectomized rats was significantly decreased after the treatment of HGH.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CYP2C19 and FMO is somewhat higher in children versus adults; however, it is not clear whether this difference in expression is sufficient to explain greater metabolic clearance of voriconazole in children versus adults. It is interesting to note that other drugs that are predominantly metabolized by hepatic CYP2C9/19 such as phenytoin, omeprazole, and sirolimus show higher clearance in children between 2 and 10 years of age than in adults (Litalien et al, 2005;Filler et al, 2008;Kennedy, 2008). It would be interesting to identify drugs that are predominantly metabolized by FMO3 and examine their clearance in children versus adults.…”
Section: Discussionmentioning
confidence: 99%
“…These factors include organ maturation, body composition, changes in liver size, liver blood flow, extent of plasma protein binding, changes in the hormonal levels, and alteration in the expression and/or catalytic activity of some of the drug-metabolizing enzymes (Hines and McCarver, 2002;Kearns et al, 2003;Chen et al, 2006;Kennedy, 2008). For example, drugs that are metabolized by hepatic CYP2C9/19, such as phenytoin, omeprazole, and sirolimus, show higher clearance in children between 2 and 10 years of age than in adults (Litalien et al, 2005;Kennedy 2008;Filler et al, 2008).…”
mentioning
confidence: 99%
“…5, 2010 HEPATIC ENZYME INDUCTION AND CLINICAL PATHOLOGY DME induction, partly because of a greater liver-to-body weight ratio and differences with adults in metabolic and protein binding capacity, and renal and hepatic function (Ginsberg et al 2004;Kennedy 2008;Moreland et al 1982). Hormonal changes with puberty are thought to further influence CYP3A4 regulation (Kennedy, 2008). In an exemplary study of children receiving long-term PB and/or PHE (Aiges et al 1980), increased activity of one or more routinely measured serum hepatobiliary marker enzymes was reported in all subjects.…”
Section: Hepatobiliary Biomarker Findings In Association With Prototymentioning
confidence: 99%